Effectiveness of Economic Comics as a Learning Media on Economic Lesson - Heni Purwa Pamungkas (STAI Hubbulwathan Duri, 2022)
Learning process in the 21st century requires innovative and creative learning. Learning process requires teachers to provide learning media that attract student motivation. Learning media innovation improves student’s learning motivation. However, if the learning media tends to be boring, student’s learning motivation will decrease and have an impact on their learning outcomes. This study aims to determine the effectiveness of economic comics as a learning media for economic subjects. The research design was quasi-experimental approach with non equivalent group design method. There are two types of classes, namely the experimental class and the control class. Each class is treated differently. In experimental class, student use economic comics as a learning media, while the control class does not use comics. In this study’s, data collection method used primary data in the form of pre-test and post-test. Data analysis techniques used T-test to compare the pre-test and post-test scores of the two classes. The results of this study are: 1) there was a difference in the gain score between the control class and the experimental class; 2) the post test value of students from the experimental class is higher than the control class. From the results of the study, it can be concluded that economic comics are effectively used as learning media.